Cellular Protection and Therapeutic Potential of Tocotrienols - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN; BATIREL, SAİME (BENTHAM SCIENCE PUBL LTD, 2011)
Tocotrienols, components belonging to vitamin E members, are used as potent therapeutics in the treatment of several diseases. Recent studies suggested tocotrienol to have better activity in many situations compared to tocopherols. Tocotrienols have been shown to lower the atherogenic apolipoprotein B and lipoprotein plasma levels. Additionally, tocotrienols with their anti-tumor effect together with anti-angiogenic and anti-thrombotic effects may serve as effective agents in cancer therapy. Besides these effects, some properties such as water insolubility and low stability limit the usage of tocotrienols in the clinic. However recent studies tried to increase the bioavailability with esterification and combination use. These efforts for the clinical usage of tocotrienols which may help them to take a wide place in the clinic and additional studies are needed to identify their therapeutical mechanisms.
Keywords: Tocotrienols; atherosclerosis; Alzheimer's disease; cancer; therapy; VITAMIN-E ACTION; ALPHA-TOCOPHEROL; GAMMA-TOCOTRIENOL; OXIDATIVE STRESS; ALZHEIMERS-DISEASE; PROSTATE-CANCER; MOLECULAR-BASIS; KAPPA-B; ANTIOXIDANT PROPERTIES; DELTA-TOCOTRIENOL